2021
DOI: 10.3390/ani11102898
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dehulling on the Nutritional Quality of Lupine Seeds (Lupinus albus L.) and the Effect of Their Use in the Feed of Laying Quails on the Live Performance and Quality of Eggs

Abstract: Lupinus albus seeds from low-alkaloid varieties are a valuable alternative source of protein for reducing the dependence on soybean meal for the feeding of monogastric animals. Therefore, the aim of this research was to evaluate the dehulling influence of lupine seeds (L. albus, cv. Amiga) and the effect of their use in the laying quails feed on live performance and egg quality. A total of 200 laying quails (Coturnix japonica), with an age of 10 weeks, were randomly assigned to five experimental groups (five r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The beneficial effects of dehulling on the nutritional value of faba beans [183,188,248], lupins [249][250][251] and field peas [105,252,253] are well documented [24,31,254]. Crude protein and crude fat contents have been reported to increase by about 10-35% and 11-20%, respectively, after dehulling (Table 24).…”
Section: Improving the Feeding Value Of Grain Legumesmentioning
confidence: 98%
See 1 more Smart Citation
“…The beneficial effects of dehulling on the nutritional value of faba beans [183,188,248], lupins [249][250][251] and field peas [105,252,253] are well documented [24,31,254]. Crude protein and crude fat contents have been reported to increase by about 10-35% and 11-20%, respectively, after dehulling (Table 24).…”
Section: Improving the Feeding Value Of Grain Legumesmentioning
confidence: 98%
“…Dehulling has been shown to markedly improve the digestibility of DM [249], protein [105,249], AAs [251], starch [31,255], and AME [14,102] of grain legumes. It had been found that dehulling increased the AME by 18 and 30% for lupins and field peas, respectively, while increasing the apparent protein digestibility by 7 and 16%, respectively [56,102].…”
Section: Improving the Feeding Value Of Grain Legumesmentioning
confidence: 99%
“…Probiotic drinks can be produced from various raw materials such as grains, millet, legumes, fruits, and vegetables [15]. L. albus seeds are lowalkaloid varieties and a valuable alternative source of proteins [16]. However, depending on the species, lupines contain varying contents of toxic alkaloids [17], which partly limits their utilization.…”
Section: Introductionmentioning
confidence: 99%